Development success : historical accounts from more advanced countries - Fosu, Augustin Kwasi; World Institute for Development Economics Research (Oxford : Oxford University Press, 2013)
What lessons can be learnt from 'developed' countries that might be useful for developing and emerging economies? With an emphasis on long-term growth and development, this volume provides historical accounts on developing lessons. It covers the Nordics, Japan, Ireland, and Switzerland, and three European transition countries.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Keywords: Economic development; Developed countries; Developing countries